Visualization analysis of Tai Chi teaching research in China over the past decade based on CiteSpace software - Xu, Xiaolong (The Journal of the International Society of Chinese Health Practices, 2025)
Research Purpose: Tai Chi is a brilliant gem of Chinese traditional culture. It not only serves functions of fitness, health preservation, and self-defense but has also been widely applied in recent years in areas like school physical education and mass fitness. With the continuous advancement of the "Healthy China" strategy, the demand for the scientific and standardized teaching of Tai Chi is becoming increasingly urgent. This study focuses on the academic development trajectory of Tai Chi teaching in China, employing the CiteSpace 6.4.R1 knowledge mapping tool for visual analysis. Through multi-dimensional bibliometric analysis, it systematically investigates the characteristics of the core researcher groups, the distribution patterns of major research institutions, and the evolution of high-frequency keyword themes in this field. The aim is to reveal the internal logic of Tai Chi academic evolution, identify key nodes of innovation within the field, and thereby provide reference points for subsequent academic exploration and practical application. Research Methods: By searching the China National Knowledge Infrastructure (CNKI) database using "Tai Chi" and "Teaching" as subject terms, setting the search period from 2015 to 2024, and removing invalid literature such as conference papers and book reviews, approximately 551 articles from core academic journals (Peking University Core, CSSCI), doctoral dissertations, and master’s theses were ultimately obtained as the analysis sample for this study. Subsequently, the CiteSpace 6.4.R1 version visualization software was used to generate visual maps depicting the authors, institutions, keyword co-occurrence, and keyword clustering of the selected literature. This was done to describe the development trajectory, current status, research hotspots, and trends in Tai Chi teaching research. Research Results: 1. Zhang Changnian was the author with the highest frequency of publications, with research areas involving martial arts, traditional ethnic sports, international communication, etc., followed by Duan Limei, Cao Maojun, Hong Shengda, Dong Yuwei, Liu Junzhan, and others.2. There were 164 contributing institutions. The top ten institutions were: Beijing Sport University, Henan University, Shanghai Sport University, Jilin Sport University, Capital University of Physical Education and Sports, Chengdu Sport University, Wuhan Sport University, Hebei Normal University, Zhengzhou University, and East China Normal University.3.Keyword analysis results showed the high-frequency keywords were: Tai Chi (123 occurrences, centrality 0.72), followed by Martial Arts (40 occurrences, centrality 0.22), Teaching Design (25 occurrences, centrality 0.08), Confucius Institute (19 occurrences, centrality 0.07), Current Situation (17 occurrences, centrality 0.07), Physical Education Teaching (13 occurrences, centrality 0.03), College Students (11 occurrences, centrality 0.05), etc.4.Keyword clustering revealed eight categories: #0 Tai Chi, #1 Martial Arts, #2 College Students, #3 Countermeasures, #4 Teaching Design, #5 Universities/Colleges, #6 Traditional Culture, #7 Baduanjin (Eight Section Brocade). Research Conclusion: Through the bibliometric analysis of the selected literature, research on Tai Chi in the educational field exhibits distinct characteristics of academic concentration.1.Beijing Sport University holds the top position in publication volume by an absolute margin, demonstrating its leading role in the field of martial arts teaching.2.The series of studies conducted by scholars like Zhang Changnian and Cao Maojun focusing on teaching design and current situation investigations have further promoted the deep integration of theory and practice. This academic community, centered around universities and scholars as nodes, provides a solid foundation for the sustainable development of Tai Chi teaching research. 3. Keyword co-occurrence and clustering analysis reveal the trend of research hotspots in Tai Chi teaching. The prominence of high-frequency words such as "Martial Arts," "Teaching Design," and "College Students" reflects a shift in research focus towards cultural empowerment. In summary, driven by both policy support and methodological innovation, the Tai Chi teaching system urgently requires innovative breakthroughs through multiple dimensions such as optimization of the theoretical system, integration of intelligent technology, and collaborative policy innovation. This can not only facilitate its transformation from a carrier of traditional culture into a modern educational model but also construct a multi-dimensional development framework supporting the national fitness public service system and the global dissemination of Chinese sports culture, thereby providing sustainable development momentum for enhancing national soft power.